Association of beta blockers and mortality in adults with septic shock: systematic review and meta-analysis of randomized clinical trial - Vásquez-Tirado, Gustavo Adolfo; Quispe-Castañeda, Claudia Vanessa; Meregildo-Rodríguez, Edinson Dante; Cuadra-Campos, María; Segura-Plasencia, Niler Manuel; Arbayza-Avalos, Yessenia Katherin; Alva-Guarniz, Hugo Nelson; Guzmán-Aguilar, Wilson Marcial; Zavaleta-Alaya, Petterson (Frontiers in Medicine, 2024)
Septic shock still entails significant morbidity and mortality, with the heart being affected due to catecholamine overexpression and direct injury from sepsis. Therefore, the effect of β-blocking the receptors to improve performance is promising when attempting to reverse tachycardia and reduce mortality. Methods: We conducted a comprehensive search across five databases for studies published up to January 28, 2024, using a PICO strategy. Ten studies were identified for quantitative analysis and included in our meta-analysis. Results: Our meta-analysis evaluated 28-day in-hospital mortality risk across nine randomized controlled trials (RCTs) involving a total of 1,121 adults with septic shock. We found an association between β-blocker use and reduced overall mortality (OR 0.57; 95% CI 0.34-0.98; I²: 56%). This effect was significant in the esmolol subgroup (OR 0.47; 95% CI 0.26-0.82; I²: 32%), but not in the landiolol subgroup (OR 0.98; 95% CI 0.0-1284.5; I²: 72%). Additionally, the intervention group shows a significant reduction in HR and lactate levels, as well as an increase in stroke volume index (SVI). Conclusions: In adults with septic shock, β-blockers are associated with a reduction in 28-day in-hospital mortality, a benefit primarily observed with esmolol rather than landiolol. Furthermore, improvements in heart rate (HR) control, lactate levels, and SVI were noted. However, these findings should be interpreted with caution, and further high-quality RCTs comparing different β-blockers are necessary to better elucidate these effects.